Molecular profiling CD8+ T-cell memory inflation - Sims, S; stuart sims (2013)
Infection with murine cytomegalovirus (MCMV) induces a large population of virus-specific CD8+ T-cells that is maintained at a high frequency in the peripheral organs for the lifetime of the host. This striking response to MCMV is termed "memory inflation". It has also been shown that a similar response occurs after immunization with a non-replicating adenovirus expressing a transgene. The key features which distinguish "inflating" CD8+ T-cell memory responses from classical "non-inflating" CD8+ T-cell memory responses have not been fully defined. To determine the molecular signature of memory inflation I sorted antigen-specific cells ex vivo and compared the gene expression profiles of inflationary CD8+ T-cells to those of central memory and effector CD8+ T-cells. This data showed that memory inflation has a distinct expression profile, with high expression of KLR receptors, specific chemokine receptors such as CX3CR1, transcription factors such as T-bet and Foxk1, and survival factors, such as Bcl-XL and down regulation of inhibitory molecules such as BTLA. These inflationary cells are functional - expressing an array of cytokines, granzymes, IFN&gama;, and TNFα, and lack transcriptional features of T-cell exhaustion. Similar features were identified in CD8+ T-cells undergoing memory inflation using both the MCMV and adenovirus models. To address the turnover of these "inflationary" CD8+ T cells and their role in vivo, I created tetramers bound to the toxin saporin to specifically knock out inflationary cells. I found that they contribute to the control of viral replication, since depletion was followed by a rise in viral load and a subsequent rebound increase in the tetramer+ population. In the final chapter I addressed the role of one specific cell surface molecule, CD73, during CD8+ T-cell memory. I found that although CD73 is thought to play a role in immune regulation, CD73-/- mice showed normal memory inflation and classical non-inflationary memory development. Overall the data in this thesis define for the first time the transcriptional profile associated with CD8+ T-cell memory and show the distinct nature of this T-cell programme in vivo. Future work using further genetically modified mouse strains should allow definition of the critical molecules and pathways involved in the development of these important memory pools.